PENGARUH MODEL PEMBELAJARAN HANDS ON ACTIVITY BERBANTUAN MEDIA SCRAPBOOK TERHADAP KEMAMPUAN MENULIS CERITA FIKSI SISWA KELAS V - Rahmi; Sulfasyah; Muhammad Akhir; Akhir, Muhammad (Jurnal Pendidikan Dasar, 2024)
This research aims to examine the influence of the hands-on activity learning model assisted by scrapbook media on the ability to write fiction stories of class V Gugus II students, Patallassang District, Gowa Regency. The research method used was an experiment with a pretest-posttest control group design. The research sample consisted of 62 students who were divided into two groups, namely the experimental group which used the hands-on activity learning model assisted by scrapbook media and the control group which used the conventional learning model. The research instrument includes a test of the ability to write fiction stories. The data obtained was analyzed using descriptive and inferential statistical techniques. The results showed that there was a significant increase in the ability to write fiction stories of experimental group students compared to the control group. Multivariate Significance Test with a significant value of 0.000 < 0.05, which means that Ho is rejected. H1 is accepted, namely that there is an influence of the hands-on activity model assisted by Scrapbook media simultaneously on the ability to write fiction stories for class V students. The conclusion of this research is that the hands-on learning model on activity assisted by scrapbook media is effective in improving the ability to write fiction stories for class V students. The implication of this research is the need for teachers to adopt and integrate creative media such as scrapbooks in the learning process in order to improve the quality of education